Correlação entre agressividade e desempenho físico em caratecas - Alves, Jonatas Nascimento (2023)
Introduction: Karate sports practice has as its main objectives the physical and psychological development of practitioners, even if for some sports coaches’ aggressiveness in sport can be a positive behavior, remaining associated with achievements in sports practice. Therefore, the present project aimed to identify the relationship between levels of aggressiveness and levels of physical performance in karateka, namely power in the vertical jump and reaction time in the application of blows (punch and kick), and to relate levels of aggressiveness with Karate practice time. Methodology: The study was based on a composting obedience sample of 8 karateka from the city of Campo Grande - MS, contact karate practitioners, with a minimum blue belt and a maximum black belt 2nd dan, with a practice time of 173 months (±25.6), age 27 years (±2.28) and all male. After completing the informed consent form, anamnesis was performed, anthropometric data were collected and the Buss-Perry Questionnaire was applied to identify the athletes' aggressiveness levels. Subsequently, the karateka performed a standard karate warm-up, then the power of 3 counter-movement vertical jumps were collected, then the reaction time of two Karate blows – a punch and a kick – were collected. Statistical analysis: Data were analyzed using Jamovi 1.1 and Microsoft Excel and are presented as Mean ± Standard Deviation. The Shapiro-Wilk normality test was performed, using Pearson's collaborator coordinator between the variables of aggressiveness and sports performance (reaction time and power of the vertical jump), practice time and level of aggressiveness, relationship of time of punch reaction and kick reaction time, relationship of vertical jump power with punch reaction time and kick reaction time. Results: A strong negative correlation was found between practice time and scores obtained for anger and the BPAQ total result (r=-0.89 and r=-0.77, respectively), moderate negative correlation between practice time and scores obtained for physical aggressiveness, verbal aggressiveness and hostility (r=-0.64, r=-0.54 and r=0.53, respectively). Between the variables Jump power and total BPAQ a weak positive correlation was found (r=0.41), reaction time of the punch and total BPAQ a weak positive correlation was found (r=0.25), reaction time of the kick and total BPAQ weak positive correlation was found (r=0.16). However, between the correlations between vertical jump power and punch reaction time, a weak positive relationship was found (r=0.25) and for the correlation between vertical jump power and kick reaction time, a moderate positive correlation was found (r=0.58). For the correlation between punch reaction time and kick reaction time, a strong positive relationship was found (r=0.90). Conclusion: The findings of our study suggest that longer karate practice time is associated with lower levels of aggression, and levels of aggression are not related to indirect karate performance, and karate athletes have a high correlation in reaction time between lower and upper limbs.